2015
DOI: 10.20344/amp.5541
|View full text |Cite
|
Sign up to set email alerts
|

Comorbilidades Psiquiátricas Associadas às Cefaleias: a Experiência da Consulta de Ligação

Abstract: Introduction:The comorbidity between headaches and psychiatric disorders is common and may be explained by different mechanisms in terms of uni or bi-directional models, or sharing of genetic and environmental risk factors relating to development of both clinical conditions. The presence of this comorbidity has important implications for patients with headaches and for patients with psychiatric disorders, worsens the clinical situation, increases the risk of chronicity, the pain intensity and the rate of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…1,34 The coexistence of headache and mental disease appears to worsen the clinical situation and increase the risk of chronicity, pain intensity, and the rate of treatment failure. 1,32 In our study, 28% of patients with a primary diagnosis of headache had at least one psychiatric comorbidity, often in the form of mood and anxiety disorders, in agreement with other studies. 1,32,33,35,36 Some authors suggested that these two psychiatric disorders are approximately two to 10 times more prevalent in patients with migraine than compared to general population.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…1,34 The coexistence of headache and mental disease appears to worsen the clinical situation and increase the risk of chronicity, pain intensity, and the rate of treatment failure. 1,32 In our study, 28% of patients with a primary diagnosis of headache had at least one psychiatric comorbidity, often in the form of mood and anxiety disorders, in agreement with other studies. 1,32,33,35,36 Some authors suggested that these two psychiatric disorders are approximately two to 10 times more prevalent in patients with migraine than compared to general population.…”
Section: Discussionsupporting
confidence: 92%
“…1,32 In our study, 28% of patients with a primary diagnosis of headache had at least one psychiatric comorbidity, often in the form of mood and anxiety disorders, in agreement with other studies. 1,32,33,35,36 Some authors suggested that these two psychiatric disorders are approximately two to 10 times more prevalent in patients with migraine than compared to general population. 1,33,35,36 In migraine patients, the prevalence of depressive disorders was variable according to studies and methodology, varying between 6.1% to 73.7%, 1,33 and twice as frequent in patients with chronic versus episodic migraine.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations